2021
DOI: 10.1177/26320770211010820
|View full text |Cite
|
Sign up to set email alerts
|

Public Opinions About Child Maltreatment in South Carolina: Salience, Relevance, Prevention, and Support for Government Intervention

Abstract: Substantial evidence demonstrates that child maltreatment is preventable through approaches that address the socio-environmental contexts that shape attitudes and behaviors. Understanding opinions about child maltreatment can inform efforts to influence policy and practice changes that promote child health and well-being. This study examined public opinions about child maltreatment in South Carolina. A telephone survey was conducted in Fall 2019 with a random sample of adults ( N = 1,145) in the state. Respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Major categories of PCEs identified by the literature include (1) after-school activities, (2) volunteering in a community, school, or church, (3) mentoring for advice or guidance, (4) sharing ideas with caregivers, (5) living in safe neighborhoods, (6) living in supportive neighborhoods, and (7) family resilience. Studies have shown that interpersonal solid support from parents or peers can enhance the mental health of adolescents [13] and that SSNRs decrease the odds of risky behavior, particularly among individuals who have experienced multiple ACEs [14]. However, adolescents with multiple ACEs may often have less access to interpersonal support.…”
Section: The Role Of Protective Factors In Mitigating the Impact Of A...mentioning
confidence: 99%
“…Major categories of PCEs identified by the literature include (1) after-school activities, (2) volunteering in a community, school, or church, (3) mentoring for advice or guidance, (4) sharing ideas with caregivers, (5) living in safe neighborhoods, (6) living in supportive neighborhoods, and (7) family resilience. Studies have shown that interpersonal solid support from parents or peers can enhance the mental health of adolescents [13] and that SSNRs decrease the odds of risky behavior, particularly among individuals who have experienced multiple ACEs [14]. However, adolescents with multiple ACEs may often have less access to interpersonal support.…”
Section: The Role Of Protective Factors In Mitigating the Impact Of A...mentioning
confidence: 99%